Fermi levels of FCC and FCT hydrides of Ti and Zr - Kandasamy, K.; Surplice, N.A. (My University, 1984)
Measurements of the work functions of films of TiHx and ZrHx during the FCC/FCT transition have given the change of Fermi level between these two phases of the hydrides. The results agree with modern calculations of the band structures of these hydrides.